Biomaterial-Driven Immunomodulation: Cell Biology-Based Strategies to Mitigate Severe Inflammation and Sepsis - Lasola, Jackline Joy Martín; Kamdem, Henry; McDaniel, Michael W.; Pearson, Ryan M. (Frontiers in Immunology, 2020)
Inflammation is an essential component of a wide variety of disease processes and oftentimes can increase the deleterious effects of a disease. Finding ways to modulate this essential immune process is the basis for many therapeutics under development and is a burgeoning area of research for both basic and translational immunology. In addition to developing therapeutics for cellular and molecular targets, the use of biomaterials to modify innate and adaptive immune responses is an area that has recently sparked significant interest. In particular, immunomodulatory activity can be engineered into biomaterials to elicit heightened or dampened immune responses for use in vaccines, immune tolerance, or anti-inflammatory applications. Importantly, the inherent physicochemical properties of the biomaterials play a significant role in determining the observed effects. Properties including composition, molecular weight, size, surface charge, and others affect interactions with immune cells (i.e., nano-bio interactions) and allow for differential biological responses such as activation or inhibition of inflammatory signaling pathways, surface molecule expression, and antigen presentation to be encoded. Numerous opportunities to open new avenues of research to understand the ways in which immune cells interact with and integrate information from their environment may provide critical solutions needed to treat a variety of disorders and diseases where immune dysregulation is a key inciting event. However, to elicit predictable immune responses there is a great need for a thorough understanding of how the biomaterial properties can be tuned to harness a designed immunological outcome. This review aims to systematically describe the biological effects of nanoparticle properties—separate from additional small molecule or biologic delivery—on modulating innate immune cell responses in the context of severe inflammation and sepsis. We propose that nanoparticles represent a potential polypharmacological strategy to simultaneously modify multiple aspects of dysregulated immune responses where single target therapies have fallen short for these applications. This review intends to serve as a resource for immunology labs and other associated fields that would like to apply the growing field of rationally designed biomaterials into their work.